PEMBERDAYAAN KELOMPOK TANI MELALUI EDUKASI DAN DEMONTRASI PEMBUATAN PUPUK KOMPOS LIMBAH RUMAH TANGGA DI DESA PAGAR AGUNG - Najwa Nurul Izzah; Putri Utami; Muhammad Jadid; Theresia Ike Shelda Sari; Aini Fauziah; Dian Meiza Putri; Septia Yunaningsih; Nabila Putri Rizqullah; Tiur Enggelina; Nada Naqiyya Affan; Rizka Al Humaira Wiliansa Putri; Syaira Salsabila; Aisah Khairani Verzulia (PARIPALAKA SRIWIJAYA, 2025)
The issue of household waste management, especially organic waste, remains a serious challenge in rural areas. A lack of understanding and skills among the community in managing organic waste leads to waste accumulation, which negatively impacts the environment and public health. Organic waste such as vegetable scraps, fruit peels, and leaves is often discarded improperly or burned. In fact, such waste has great potential to be converted into compost fertilizer that can benefit local agriculture. This activity aimed to improve the knowledge and skills of farmer groups in Pagar Agung Village through food security education and demonstrations on making compost from household waste. The methods included interactive lectures using PowerPoint media and hands-on compost-making practices. A total of 26 participants of various age groups took part in the program. Evaluation was conducted using pre-test and post-test questionnaires, each consisting of 10 true-or-false questions, and an interactive quiz to assess participant engagement. The results showed a significant increase in knowledge after the activity. More than 80% of participants answered most post-test questions correctly, with five questions answered correctly by all participants (100%). Furthermore, there was increased understanding of the link between household waste management and family food security. The educational method applied effectively increased interest and ability in processing organic waste. This activity serves as an effective strategy for community empowerment to create a healthy environment and support sustainable food security.